الاختصاصات التشريعية والمالية لمجالس المحافظات غير المنتظمة في إقليم - عامر محمد علي أبو نايلة (Journal of Madenat Alelem University College, 2010)
Distinguish the concept of state simple form of monopolizing power, however, ruling class to dominate all the authorities and holding the reins fully. However, in the beginning of the sixteenth century dawned, taking factors are pushing heavily on this mode is concentrated in two ways: First: the growing awareness and promote the intellectual among the people and failure to submit to the oppressive authorities, and the second: for economic and social developments and complexity and diversity of the needs of the community, which has become impossible to the central authority to satisfy those needs. The concentration of power is a serious obstacle in completing the development projects and services better .And diverse and distributed power in various forms, including delegation of authority from the president to his stuff or decentralized regional or political decentralization. In short, intended to decentralize the administrative function is the distribution between the central government and created local and other words that decentralization lead to the transfer of power in decision-making to local bodies. In order for the central administration to the principle of democracy the truth go to most scholars that the independence of decentralized bodies can never be true unless the election of members of those bodies, but some maintain that they include members appointed by the central authority. The principle of central administrative palace is a management function in the state on the authority of one, even from multiple government bodies as long as the occupants are subject to the authority of one presidential term and the rules and regulation of one. Decentralization means a short, that there are multiple authorities in the state of the one type does not have any authority in the state and one of the authorities of the three types of "legislative, executive, judicial" but where more than one authority, one of each type such authorities or some of them. The many types of decentralization mismatch political decentralization and administrative decentralization, as the latter take the most important of several types of administrative decentralization taking the absolute by the constitution for the Iraqi governorates boiled non-regular in the region.